2017
DOI: 10.1038/s41598-017-01321-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerance of propranolol in neonates with severe infantile hemangiomas: a prospective study

Abstract: Although the efficacy of propranolol for the treatment of infantile hemangiomas (IHs) has been well documented, there is a paucity of clinical data regarding the safety and tolerance of propranolol in neonates. A prospective study of 51 patients less than 30 days of age with severe IH was conducted. All patients were admitted to the hospital for monitoring during initial propranolol treatment at day 0 with dose adjustments at days 7 and 28. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
4
28
0
1
Order By: Relevance
“…In our study, 70 (16.0%) patients experienced AEs, and the frequencies of the top 4 AEs, from high to low, were as follows: 27 (38.8%) diarrhea, 11 (15.7%) sleep problem, 5 (7.1%) increased stool frequency, and 4 (5.7%) emotion problem. There were only 2 (2.9%) respiratory problems in our study, which may occur because children with a history of neonatal pneumonia are more likely to have respiratory disorder [27]; however, all patients included in our study did not have such a history. There was no asymptomatic hypotension or bradycardia observed; because we did not measure blood pressure in the routine follow-up [28, 29], hand-held pulse oximeter was used by parents for self-test and out-patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 70 (16.0%) patients experienced AEs, and the frequencies of the top 4 AEs, from high to low, were as follows: 27 (38.8%) diarrhea, 11 (15.7%) sleep problem, 5 (7.1%) increased stool frequency, and 4 (5.7%) emotion problem. There were only 2 (2.9%) respiratory problems in our study, which may occur because children with a history of neonatal pneumonia are more likely to have respiratory disorder [27]; however, all patients included in our study did not have such a history. There was no asymptomatic hypotension or bradycardia observed; because we did not measure blood pressure in the routine follow-up [28, 29], hand-held pulse oximeter was used by parents for self-test and out-patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, there is evidence suggesting that the blood-brain barrier in young infants is immature and selectively permeable and differs substantially from that of adults; this difference may facilitate the penetration of propranolol 27 . In addition, recent studies demonstrated that young infants who have a history of apnea or neonatal pneumonia appear to be at higher risk for bronchial hyperreactivity after the initiation of β-blocker treatment 28 , 29 . Bronchial hyperreactivity is a direct effect of non-selective β-blockers (e.g., prapranolol) due to β 2 -AR blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Although propranolol treatment is effective in both arresting growth and causing involution, irreversible sequelae may have already occurred. These observations, together with the work presented here, promote the recommendation that, in patients with severe IHs, oral propranolol should be administered as early as possible to avoid potential complications [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 53%